The Role of Sarvak Formation in Supplying Pol-e Dokhtar Town (Iran) with Drinking Water - Ahmadipour, Mohamad Reza (Acta Carsologica, 2016)
Formacija Sarvak je najbolj zakrasela formacija v skupini Bagestan, SZ od mesta Pol-e Dokhtar. Njeno južno krilo je zakraselo in najpomembnejše za talno vodo. Za oskrbo s pitno vodo mesta Pol-e Dokhtar, so bili izvrtani trije vodnjaki. Opravljen je bil črpalni (72 ur). Analize kisika-18 in devterija kažejo na meteorni izvor vode. Voda iz vodnjaka W1 ima minimalno, iz W3 pa maksimalno koncentracijo tricija, kar kaže na različen rezidenčni čas, kemične analize pa, da gre za vode tipa Ca>Mg>Na in HCO3 >SO4 >Cl. Med samim vrtanjem so imeli vzorci vode relativno veliko količino NO3 (27 mg/l), ki se je, zaradi zavarovanja področja pred kmetijsko dejavnostjo, znižala. Mesto Pol-e Dokhtar, ki je imelo resne težave z oskrbo s pitno vodo že izpred časov islamske republike, teh zdaj nima več, zahvaljujoč predstavljeni raziskavi. The Sarvak formation is the most karstified formation of the Bageston group, NW from town Pol-e Dokhtar. Its southern limb is karstified and the most important for the ground water. Three wells were drilled for supplying the drinking water to Pol-e Dokhtar. The pumping test (72 hours) was carried out. Analyses of oxygen-18 and deuterium indicated that the water is of meteoric origin. Water from the well1 has the minimal and from the well3 maximal concentrations of tritium which indicate different residence time. Chemical analyses show that the water is of Ca>Mg>Na and HCO3>SO4>Cl type. During the drilling water samples had relatively high NO3 (27 mg/l), which was reduced due to the protection of the area from agricultural activities. Due to this study, the town of Pol-e Dokhtar, which was facing serious problem of drinking water since before the Islamic Republic of Iran, has been solved.